Precepting medical students in the clinical setting: Its time, not money. Issue 7 (23rd May 2022) - Martinez, Guadalupe Federico; Knox, Kenneth S.
Abstract : Martinez and Knox reflect on the many contextual factors that influence motivations to remain engaged in education through reaction to Hatfield et al.'s challenge of the belief that clinical precepting reduces productivity.